Semantic Aspect of Methodical Training of Faculty Members (Recursive Model) - Sotnikova, Olga Aleksandrovna (International Review of Management and Marketing, 2016)
Components of methodical training of faculty members at higher education institutions, determining efficiency of using pedagogical technologies, are investigated in this paper. The author studies semantic aspect of methodical training of faculty members at higher educational institutions – the competency to organize student work on making sense of studied conceptions and texts. We substantiate from psychological and pedagogical perspective that semantic analysis is basic for faculty members to carry out different kinds of professional activity. Based on methodological analysis, learning actions composing the essence of semantic analysis are revealed: establishing relations in studied material like juxtaposing scope and content of conceptions, reflecting the sense (conception) and the meaning (denotation) of names of conceptions. Combination of those actions represents the essence of understanding process while working with educational text. Examples from mathematics course, demonstrating the distinguishing features of semantic analysis, are given. The author offers the technology of training in shaping skills in making semantic text analysis in recursive model of methodical training, built in accordance with cyclic principle. Every cycle of the technology includes methodologic, information and training stage of shaping skills in making semantic text analysis. Recursive technology use in shaping methodical competency of faculty member will make possible to boost solving topical problems of Russian higher education system. Keywords: Making sense in educational cognition, hermeneutic trend in education, educational text, semantics of educational text JEL Classifications: B410, I230, J820